CEPHALIC TETANUS A RARE LOCAL TETANUS - Iin Novita Nurhidayati Mahmuda; Doni Priambodo (Universitas Muhamadiyah Surakarta, 2015)
Woman, 68 years old came to hospital with chief complain trismus and dysphagia. She was in a good condition with physical examination and standard laboratory test reveal normal value. The neurologist found multiple parese of cranial nerve (V, VII, IX, X, XI). After further examination include electromedic test and head ct scan with contrast the neurologist did not find any abnormality that may explain her symptoms. The patient then consulted to the internist with suspect of local tetanus infection because of focal infection in her dental caries. The patient is then treated with antibiotics, convultion inhibitor agent, also given tetanus immunoglobulin. During the treatment, her symptoms improved. There were no other severe complication. Patient was returning home on the ninth day of hospitalisation and ready for her dentist appointment.Keywords : Trismus, dysphagia, parese, tetanus, tetanus imunoglobulin